Intellectual spiritual intelligence in akhlaq development from the perspective of Islamic philosophy / Hamdi Rahman Mohd Yaacob … [et al.] - Mohd Yaacob, Hamdi Rahman; Zainal Abidin, Mohd Zahirwan Halim; Hassan, Paiz; Yusof @ Salleh, Muhammad Yusri (Center for Islamic Philantrophy & Social Finance (CIPSF), 2023)
The works on the interpretation of Al-Quran dating from the beginning of the sixth century of the hijrah or the thirteenth century (AD) is replete with commentaries related to the perfection of two intellectual intelligences which are theoretical intelligence and practical intelligence in the pursuit of contentment in the world and the hereafter through akhlaq development. This incentive raises questions regarding the relationship between the two intelligences and the development of akhlaq from the Islamic perspective. Adopting the document review approach, this study aims at explaining the role of the two intelligences pertaining akhlaq development in a more practical manner by referring to the Islamic philosophical thinking circulated during the abovementioned period. The findings identified a model of spiritual intellectual intelligence that explains the relationship between different intelligences from the Islamic perspective. The model concludes that sound akhlaq conjectures are the impact of certain positive motivations resulting from the process of imagination or repetitive thinking in applying certain Islamic knowledge.